A comparison of self-complexity in the United States and South Korea. Issue 1 (2nd January 2017) - Brown, Christina M.; Shilling, Aaron A.; Park, Sun W.
Abstract: Self-complexity, a measure of self-concept structure consisting of number of self-aspects and relatedness of self-aspects, was compared in the United States and South Korea. University students in each country completed measures of self-complexity and self-construal. In two studies, participants from South Korea had more self-aspects and overall self-complexity (as measured by H ) than participants from the United States. Self-construal was not responsible for these differences. In addition, a comparison of previous self-complexity research carried out in different countries supports the conclusion that people from East Asian countries have more self-aspects than people from the United States. The results are discussed in terms of broader cultural differences in psychological phenomena.